Bio-Inspired Engineering: Nature-Inspired Solutions for Sustainable Design - Tobias Merrick Vaughn; Flynn Archer; Callum Sloane (Proceeding of the International Conferences on Engineering Sciences, 2024)
Bio-inspired engineering is a rapidly growing field that applies principles found in nature to develop innovative solutions in structural engineering, materials science, and robotics. This paper explores biomimicry in various disciplines, such as self-cleaning surfaces inspired by lotus leaves, energy-efficient building designs modeled after termite mounds, and ultra-lightweight yet durable materials inspired by spider silk. The study highlights the role of computational modeling in replicating biological structures and discusses the challenges of translating natural efficiencies into engineered systems. Additionally, this research examines the environmental impact of bio-inspired materials and their potential to replace conventional, resource-intensive materials in industries such as construction, aerospace, and biomedical engineering.